The difference in histological grades of endometrial carcinoma in curettage and hysterectomy : cross-sectional study = Razlika histološkog gradusa karcinoma endometrija u kiretaži i histerektomiji : presječna studija - Franjić, Barbara Sabrine (Array, 2020)
Objectives: To determine the compatibility rate between histological grades of endometrial carcinoma in curettage and hysterectomy and to determine how quantity of material, given by the method of fractional hysterectomy, affects the compatibility between histological grades in the two methods. Material and methods: The study included 102 patients with endometrioid endometrial cancer who underwent methods of fractional curettage and hysterectomy. Data regardingthepathohistological status of uterine tissue was obtained from the available medical records. Information on age andclinical diagnoses were obtained from referrals for pathohistologicaltissue examination. The age of the subjects was determined at the time when the tissue samples were taken for analysis. Data on the amount of material was obtained from the description of macroscopic evaluation of the given material. Results: Most subjects had grade II endometrioid endometrial cancer (47.1 % and 50 %). Most of the respondents had a medium deficient material obtained by fractional curettage (40.2 %). There was no statistically significant difference between the histological grade determined after the fractional curettage and hysterectomy. There were no statistically significant differences in histological grade in the sample obtained by fractional curettage and hysterectomy depending on the amount of material in fractional curettage. Conclusions: There was no statistically significant differences in the grade of endometrial cancer in samples obtained by the fractional curettage and hysterectomy. The correspondence is higher in higher tumor grade (III), and lower in lower tumor grades (I, II). The amount of material did not affect the grade deviation in the sample obtained by fractional curettage and hysterectomy.